Expectations of Educational Continuity among Beneficiary Families of the Indonesian Conditional Cash Transfer (PKH): A Case Study in Tabuan Island, Tanggamus Regency - Nugroho, Setiyo; Listyaningsih, Umi; Pitoyo, Agus Joko (Populasi, 2023)
Implemented since 2007, The Indonesian Conditional Cash Transfer (PKH) program aims to alleviate poverty by encouraging education participation among the impoverished. Analyzing the educational expectations of PKH beneficiaries is crucial for program’s impact evaluation. Changes in educational expectations indicate the awareness of poor families to invest in education. Moreover, examining socio-economic impacts on educational expectations offers insights into challenges faced by impoverished families. This study, conducted on Tabuan Island in Tanggamus Regency which is a remote area with inadequate educational facilities, investigates the impact of PKH over 15 years by 2022. Using primary data from two groups: PKH beneficiary families (intervention) and non-PKH families (control) – the research quantitatively compares their educational expectations. Further exploration involves logistic regression tests to examine socio-economic factors’ influence on the intervention group. Results reveal PKH’s positive impact on elevating beneficiary families’ educational expectations. The analysis showed significantly higher educational expectations among PKH families compared to non-PKH families, particularly when excluding other educational assistance. PKH beneficiaries are estimated to be 10,269 times more likely to expect their children to graduate from college than non-PKH families. Internet access in the last 3 months, and participation in P2K2 counseling, have a positive impact on the PKH beneficiary families’ educational expectations. This highlights the importance of positive educational information and the potential of information technology in supporting their children’s education. However, it is concerning that despite having high expectations, families receiving PKH on Tabuan Island face challenges in ensuring their children’s access to college education.